Thermoregulation, fluid balance, and sweat losses in American football players - Davis, J. K.; Baker, L. B.; Barnes, K.; Ungaro, C.; Stofan, J. (Sports Medicine, 2016)
Numerous studies have reported on the thermoregulation and hydration challenges athletes face in team and individual sports during exercise in the heat. Comparatively less research, however, has been conducted on the American Football player. Therefore, the purpose of this article is to review data collected in laboratory and field studies and discuss the thermoregulation, fluid balance, and sweat losses of American Football players. American Football presents a unique challenge to thermoregulation compared with other sports because of the encapsulating nature of the required protective equipment, large body size of players, and preseason practice occurring during the hottest time of year. Epidemiological studies report disproportionately higher rates of exertional heat illness and heat stroke in American Football compared with other sports. Specifically, larger players (e.g., linemen) are at increased risk for heat ailments compared with smaller players (e.g., backs) because of greater body mass index, increased body fat, lower surface area to body mass ratio, lower aerobic capacity, and the stationary nature of the position, which can reduce heat dissipation. A consistent finding across studies is that larger players exhibit higher sweating rates than smaller players. Mean sweating rates from 1.0 to 2.9 L/h have been reported for college and professional American Football players, with several studies reporting 3.0 L/h or more in some larger players. Sweat sodium concentration of American Football players does not seem to differ from that of athletes in other sports; however, given the high volume of sweat loss, the potential for sodium loss is higher in American Football than in other sports. Despite high sweating rates with American Football players, the observed disturbances in fluid balance have generally been mild (mean body mass loss =2 %). The majority of field-based studies have been conducted in the northeastern part of the United States, with limited studies in different geographical regions (i.e., southeast) of the United States. Further, there have been a limited number of studies examining body core temperature of American Football players during preseason practice, especially at the high school level. Future field-based research in American Football with various levels of competition in hotter geographical regions of the United States is warranted.